MODALITAS TERAPI KERATOSIS SEBOROIK MENGGUNAKAN ELEKTRODESIKASI – SEBUAH LAPORAN KASUS: A Therapy for Seborrhoic Keratosis Uses Electrodesication – A Case Report - Andre Parmonangan Panjaitan; Lovina Ramaditha Agung; Yulisna (Forind Press, 2024)
Seborrhoeic keratosis is a benign tumor of the epidermis derived from keratinocytes. Benign proliferation of immature keratinocytes causes seborrheic keratosis, which presents as flat, well-defined, round, or oval macules. Lesions occur predominantly in middle age but can present in early adolescence and are more common in whites. The causative factor for seborrheic keratosis remains uncertain, though several factors that trigger seborrheic keratosis include genetics, ultraviolet radiation, and infection. Mrs. S, 56, housewife. The patient, since 2019, complained of light brown-dark brown pimples on her face and body. He had a history of hypertension, diabetes mellitus, a history of stroke, Alzheimer's, and a family history of similar complaints. Patients rarely use sunscreen when doing the activities. Dermatological status: hyperpigmented papules with extrinsic borders, multiple, round-irregular shape, miliary-lenticular size, verrucous surface, and discretely arranged regional distribution. Treatment is by electrodessication. This is a process that is therapeutic to remove superficial epidermal lesions without invading the dermis. This technique requires local anesthesia and can be performed at the Dermatology and Venereology Polyclinic.